Strategic innovation: The case of ‘Tata Nano’ - Goyal, Megha (2010)
In recent years there has been increased interest in innovations as a source of competitive advantage. For many years, it was believed that innovations are the tools of new entrants to gain rapid market share especially in markets with high barriers to entry. But in recent years, many established players (e.g. Apple, Sony and Tata motors) have led their respective industries in terms of strategic innovations. This research investigates different aspects of strategic innovations using Tata Nano as a case study. The purpose of this research is to understand the process of innovation, factors that assist or create barriers in firm’s ability to innovate and organisational factors which lead to the success of innovation.